Ho Chi Minh’s thought on talents and issue of developing talented civil servants in Vietnam today - Dung, Nguyen Thi Thanh; Hong, Le Thi Thu (International Journal of Innovative Research and Scientific Studies, 2025)
Ho Chi Minh - The great leader of the Vietnamese people, devoted his whole life to the country and the happiness of the Vietnamese people; internationally, he was honored as a world cultural celebrity for his many outstanding contributions to the progress of humanity. In Vietnam today, the political line is determined based on Ho Chi Minh’s ideology. Accordingly, Ho Chi Minh’s ideology serves as the compass for the leadership activities of the Communist Party of Vietnam and the management activities of the Vietnamese state. This study addresses a specific aspect of Ho Chi Minh’s ideology, which is the issue of talent and its application to develop talented civil servants for public service in Vietnam. Based on the analysis of Ho Chi Minh’s thoughts on talent, the author builds a theoretical research model on talented civil servants and conducts a survey of 330 leaders from 180 local government agencies at the commune level, representing three regions of Vietnam, including Hai Phong city (North), Hue city (Central), and Can Tho city (South). The survey results serve as the basis for the author to draw research conclusions and discuss policy issues to develop talented civil servants in Vietnam in the context of the current development of digital government and digital society.